Robotic assistance during cochlear implantation: the rationale for consistent, controlled speed of electrode array insertion - Kashani, Rustin G.; Henslee, Allan; Nelson, Rick F.; Hansen, Marlan R. (Frontiers in Neurology, 2024)
Cochlear implants (CI) have revolutionized the treatment of patients with severe to profound sensory hearing loss by providing a method of bypassing normal hearing to directly stimulate the auditory nerve. A further advance in the field has been the introduction of “hearing preservation” surgery, whereby the CI electrode array (EA) is carefully inserted to spare damage to the delicate anatomy and function of the cochlea. Preserving residual function of the inner ear allows patients to receive maximal benefit from the CI and to combine CI electric stimulation with acoustic hearing, offering improved postoperative speech, hearing, and quality of life outcomes. However, under the current paradigm of implant surgery, where EAs are inserted by hand, the cochlea cannot be reliably spared from damage. Robotics-assisted EA insertion is an emerging technology that may overcome fundamental human kinetic limitations that prevent consistency in achieving steady and slow EA insertion. This review begins by describing the relationship between EA insertion speed and generation of intracochlear forces and pressures. The various mechanisms by which these intracochlear forces can damage the cochlea and lead to worsened postoperative outcomes are discussed. The constraints of manual insertion technique are compared to robotics-assisted methods, followed by an overview of the current and future state of robotics-assisted EA insertion.